Texture classification using neural network - Mohd Yahyal, Haq Muslan (Fakulti Sains dan Teknologi, 2011)
Texture is one of the attributes commonly used in image analysis and pattern recognition. At this moment, there is no single method that could be used to classify all type of textures resulting from the complexity in variation of texture. Besides, several popular techniques have been reported to have high classification accuracy for certain type of texture.